FRI0495 What Might be the Factors for Staying in Remission in JIA? Data from the German Biker Registry. (9th June 2015) - Peitz, J.; Becker, I.; Horneff, G.
Abstract : Background: Remission is a goal of modern treatment of JIA and can be achieved by numerous patients upon intense treatment with methotrexate, biologics or combinations. It remains unclear how many patients have sustained remission after discontinuation being off drugs. Methods: In the German BIKER Registry we retrospectively analyzed the data of 3610 patients treated for juvenile idiopathic arthritis (poly or systemic) either with methotrexate or biological agents, for remission rate, flare rate after remission and whether there are factors predictive for staying in remission. Due to the small number of patients treated with adalimumab, followed in the registry only since 2012, we concentrated on 3387 patients treated either with etanercept (ETA) (1870) or methotrexate (MTX) (1517). Results: In the MTX group 29.7% (451/1517) got into remission and ended treatment. In the ETA group 21.1% (395/1870) patients got into remission. Due to incomplete data for the issue we finally got 587 data sets left. In these data we found several statistically significant positive predictive factors for staying in remission (table ). Non predictive factors were: antinuclear antibody positivity, CCP antibody positivity, HLA B27 carriership, age at disease onset, age at start of therapy (SOT), duration of therapy, patient VAS at SOT, number of active joints at SOT, JADAS10 at SOT or EOT, ESR at SOT or end of therapy (EOT), LOM at SOT or EOT, physicians VAS at EOT, JIA category other than systemic arthritis, NSAR at SOT or EOT, concomitant treatment with glucocorticosteroids at SOT or EOT, therapy with sulfasalazine, azathioprine, cyclosporine, NSAIDs or glucocorticoids before starting MTX or ETA therapy, ongoing MTX therapy after ending an ETA therapy. Conclusions: The Biker registry primarily is a pharmacovigilance instrument with the objectives of surveillance of safety. Retrospectively we were able to find a small number of predictive factors for staying in remission off therapy. Hazard ratios of statistically significant factors however were rather low. Disclosure of Interest: None declared